Psikologi ulayat - Sarwono, Sarlito Wirawan (Konsorsium Psikologi Ilmiah Nusantara, 2012)
Classical psychology tends to be conservative. It deals merely with universal theories concerning individual processes. The trend towards more social oriented paradigms started when European psychologists Serge Moscovici raised the issue of social representation (1961), and Henrri Tajfel and Turner published their theories on Social Identity (1979). Psychology is no longer individual. It is related to social and cultural environment. Each group, race or ethnic has its own psychology, which is relevant to their respective context. In 1933, an Asian Psychologist, Uichol Kim and his European colleague John Berry initiate the term indigenous psychology that is defined as â€the scientific study of human behavior or mind that is native, that is not transported from other regions, and that is designed for its peopleâ€. Since there is no matching Indonesian word for â€œindigenousâ€, in an Indonesian Social Psychology Association Conference held at the University of Indonesia, Jakarta, in 1999, I coined the word â€œulayatâ€. I borrowed the term from anthropology and the adat (traditional) law that means almost similar to Kim and Berry definition of â€œindigenousâ€. This article discusses the history, the development of theories and application of this new field in psychology in Indonesia.